Performance Measuring Factors in MSMEs in the Digital Era: Systematic Literature Review - Indira Oktavianti; Sudarmiatin Sudarmiatin; Agus Hermawan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to systematically review performance measuring factors in MSMEs in the digital era in Indonesia. The research method uses Systematic Literature Review (SLR) with the design of the PRISMA framework. The data sources used were obtained from various databases of quality scientific publications including emerald, taylor and francis, springerlink, and sciencedirect, with a time span from January 2020 to June 2025. A total of 24 international scientific articles published in the period were analyzed for further identification on the main trends, main topics, and research directions. The results of the study show that the role of digital transformation has become an important factor in shaping the performance of MSMEs in the modern era. The factors that measure the performance of MSMEs are related to entrepreneurial competence, adaptation to technology, innovation ability, and government support. Some of these supporting factors also support resilience and sustainability for micro, small, and medium enterprises (MSMEs). However, the success of work achievements for business actors cannot be separated from adequate organizational readiness and resources, as well as good governance. This study contributes academically in the form of a conceptual framework for performance improvement measures for MSMEs, as well as providing recommendations as strategies for micro, small, and medium business actors to increase productivity so that businesses can grow and be sustainable in the digital era.